Implication of Institutional Frameworks Governing Land Tenure Security in Social-Economic Dynamics: Experience from Iringa District in Tanzania - Usika, Gerald; Urassa, Justin; Kabote, Samwel (Journal of Public Policy and Administration, 2024)
Purpose: The study aimed to examine the implication of institutional frameworks governing land tenure security in socioeconomic dynamics in the Iringa district. The study used the case of the Iringa district to investigate the institutional framework that provides implications for the governance of land tenure security in Tanzania. Methodology: The study employed phenomenography by collecting primary data from 16 key informants selected from village and district levels. Data from key informants were complemented by documentary review with perception considered deductively. Findings: Findings confirmed the existence of two principal institutional frameworks; the Land Act No. 5 of 1999 and the Village Land Act No. 4 of 1999. Nonetheless, bureaucracy, inadequate policy dissemination, and poverty emerged as primary causes of deviations in land policy implementation in the study area. This study concludes that the successful implementation of Tanzania's land policy in the Iringa District Council has significantly facilitated land tenure security through the issuance of a Certificate of Customary Right of Occupancy. Establishing a robust institutional framework and clear land use rules has been central to this success. However, challenges such as complex Certificate of Customary Right of Occupancy acquisition procedures, bureaucracy, inadequate policy dissemination, and prevalent poverty in rural areas have been identified as impediments. Unique Contribution to Theory, Practice and Policy: The study was guided by Institutional Theory which describes the interaction of human beings with existing natural resources, the institution involves the regulation of formal rules from constitutions, status laws, and other legal frameworks controlling the interaction and relationship of human behavior. The study contributed to the theory by establishing the relationship between the organization and enforcement of policy and regulatory framework that governs land tenure. Also, the study recommends expanding the Certificate of Customary Right of Occupancy issuance, strengthening local land administration, simplifying land use regulations, facilitating easier access to Certificate of Customary Right of Occupancy especially for impoverished households, and implementing strategies to reduce bureaucracy and enhancing policy understanding at the grassroots level. These measures aim to enhance land tenure security and support sustainable development in rural communities.